Supporting rural/remote primary health care placement experiences increases undergraduate nurse confidence - Bennett, P.; Jones, D.; Brown, Janie; Barlow, V. (Churchill Livingstone, 2012)
This paper reports on the analysis of data fromundergraduate nursing studentswho participated in the PrimaryHealth Care Intensive Programme (PHCIP) in far west New South Wales between 2006 and 2008. This analysislooks specifically at pre/post confidence levels of participants in relation to their grasp of underlying principlesassociated with primary health care practice and Indigenous health care delivery. Bachelor of nursing curricularemains heavily weighted towards acute care in large metropolitan facilities however; universities activelyseek clinical fieldwork experiences in rural/remote and Indigenous communities for their students. The PHCIPwas developed and delivered through the Broken Hill University Department of Rural Health, University ofSydney, and sought to address the disparity in student preparedness for practice in these settings throughthe provision of a structured and educational rural and remote clinical placement experience. Pre/postquestionnaires, focus groups and three month post-placement phone interviews provided data on levelsof participant confidence in the areas of primary health care delivery and culturally knowledgeable practice.This study indicates that structured preparation for practice, underpinned by authentic learning experiencesand aligned with comprehensive education programmes can have a positive impact in the areas ofskills, knowledge and attitudes and enhance the confidence of undergraduate nurses undertaking clinicalplacements in these settings. These findings are relevant to contemporary nursing education and evolvingmodels of health care delivery for rural and remote communities.